2000
DOI: 10.1055/s-2000-9775
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hepatitis B Virus Effects of Wogonin Isolated from Scutellaria baicalensis

Abstract: By using an HBV-producing cell line (MS-G2) in vitro culture system, we found that wogonin isolated from Scutellaria baicalensis can suppress HBV surface antigen production (P < 0.001) without evidence of cytotoxicity. By assaying the endogenous HBV DNA polymerase activity, we found that both the relaxed circular and the linear forms of HBV DNA are significantly reduced in the wogonin-treated group. Wogonin deserves to be further evaluated for the treatment of human HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 5 publications
0
79
0
Order By: Relevance
“…This herb has been used for thousands of years in Asia for inflammatory diseases and also for hepatitis. The anti-HBV activity of wogonin was already reported in 2000, demonstrating its ability to suppress hepatitis B surface antigen (HBsAg) secretion in cell culture [30] . Recently, the suppression of both HBsAg and hepatitis B e-antigen (HBeAg) secretion was shown with an IC50 of 4 µg/mL [31] .…”
Section: -Arylbenzofuran Derivativesmentioning
confidence: 99%
“…This herb has been used for thousands of years in Asia for inflammatory diseases and also for hepatitis. The anti-HBV activity of wogonin was already reported in 2000, demonstrating its ability to suppress hepatitis B surface antigen (HBsAg) secretion in cell culture [30] . Recently, the suppression of both HBsAg and hepatitis B e-antigen (HBeAg) secretion was shown with an IC50 of 4 µg/mL [31] .…”
Section: -Arylbenzofuran Derivativesmentioning
confidence: 99%
“…Wogonoside has been reported to possess free radical scavenging and antioxidant activities. 4) Baicalin, baicalein and wogonin have been extensively explored to show anti-inflammatory, 5,6) antiviral, [7][8][9] free radical scavenging, 4,10) antioxidant 10,11) and anticancer activities. [12][13][14] In addition, baicalin was also shown to induce apoptosis in prostate cancer cell line.…”
mentioning
confidence: 99%
“…In the hepatitis B virus (HBV)-producing cell line (M2-G2), wogonin suppressed HBV surface antigen production without cytotoxic effect (18). Similarly, using a cytopathic effect assay, Ma et al (35) demonstrated in vitro antiviral effect of wogonin using respiratory syncytial virus (RSV).…”
Section: Antiviral Effectsmentioning
confidence: 99%